Identification the Need of Electronic-Based Physics Teaching Materials for Increasing Problem Solving Ability in the 21st Century - Lis Tyas; Harjana Harjana; Daru Wahyuningsih (Prosiding SNFA (Seminar Nasional Fisika dan Aplikasinya), 2020)
Abstract: This study aims to identify and describe the need for physics teaching materials in the 21st century to increase problem-solving abilities in high school students. The research sample in this study were students of class X SMA Al Islam 1 Surakarta. Data analysis was carried out descriptively, the data obtained in this study were data from interviews, questionnaires, student learning outcomes on Business and Energy material. The results of this study indicate that students need teaching materials in the form of learning media that support the 21st century equipped with a learning model that can improve students' ability to solve problems, namely E-module STEM-PjBL-based.Abstrak: Penelitian ini bertujuan untuk mengidentifikasi dan mendiskripsikan kebutuhan bahan ajar fisika di abad 21 terhadap peningkatan kemampuan pemecahan masalah pada siswa Sekolah Menengah Atas. Sampel penelitian dalam penelitian ini yaitu siswa kelas X SMA Al Islam 1 Surakarta. Analisis data dilakukan secara dekriptif, data yang diperoleh dalam penelitian ini berupa data hasil wawancara, angket, hasil belajar siswa pada materi Usaha dan Energi. Hasil dari penelitian ini yaitu siswa membutuhkan bahan ajar berupa media pembelajaran yang mendukung abad 21 dilengkapi dengan model pembelajaran yang dapat meningkatkan kemampuan siswa dalam memecahkan masalah yaitu E-modul berbasis STEM-PjBL